Search 73,932 tutors
0 0

# please see the bellow simulteneaus equation and help me please, i am canfused. thanks alot

3/4x+1/2y=15
1/2x+4/6y=13

3/4 X + 1/2 y = 15

1/2 X + 4/6 y = 13

Multiply the first equation by 4:

- (3X + 2Y = 60)
3X  + 4y = 78      ( 2nd equation by 6)

Now by method of elimination we subract first equation from the 2nd.

2Y = 18       Y = 9

Substitue  Y = 9

3X +18 = 60

3X = 42              X = 14

3/4x+1/2y=15
1/2x+4/6y=13

I am assuming this is...
(3/4)x+(1/2)y=15
(1/2)x+(4/6)y=13

Let's begin with the first equation...
(3/4)x+(1/2)y=15
Fractions are so confusing.  Let's note that the denominators (also known as divisors) are 4 and 2.  Let's multiply everything by 4...
4[(3/4)x+(1/2)y]=4(15)
3x+2y=60

Let's proceed with the second equation...
(1/2)x+(4/6)y=13
Let's multiply both sides by 6...
6[(1/2)x+(4/6)y]=6(13)
3x+4y=78

3x+4y=78
3x+2y=60
Let's subtract the first equation from the second...
0+2y=18
2y=18
Let's divide both sides by 2...
(2y)/2=18/2
y=9

Original equations...
(3/4)x+(1/2)y=15
Let's plug-in 9...
(3/4)x+(1/2)(9)=15
(3/4)x+4.5=15
Let's subtract 4.5 from both sides...
(3/4)x+4.5-4.5=15-4.5
(3/4)x=10.5
Let's multiply both sides by (4/3)...
(4/3)(3/4)x=10.5(4/3)
x=42/3=14

(1/2)x+(4/6)y=13
Let's plug in y=9 and x=14 to verify...
(1/2)(14)+(4/6)(9)=13
7+(36/6)=13
7+6=13